Splinting the penis for split skin grafting: Use of longitudinally split plastic syringe - Sharma Ramesh; Cyriac Chacko (Indian Journal of Plastic Surgery)
We describe a new method of splinting the penile shaft following split skin grafting for avulsion injuries of the penis. A 10 ml syringe is split longitudinally and one half is applied either dorsally or ventrally after placing absorbent dressing on the grafted area. This is then held in place with either tape or bandage.